Pendekatan Arsitektur Kontemporer dalam Perancangan Gedung Festival Seni dan Budaya Kabupaten Muna - Ridal, Ridal; Andi Halim, Haryanto; Zaki, Muhammad (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2025)
Indonesia is an archipelagic country consisting of 34 provinces with cities and districts in them. Indonesia has a diverse cultural and artistic diversity from different regions. Arts and culture centers are crucial in preserving the archipelago's artistic and cultural heritage in the midst of the increasingly rapid flow of globalization, especially among the younger generation who are vulnerable to the influence of foreign lifestyles (Amalia & Agustin, 2022). Muna Regency is an area in Southeast Sulawesi Province that started its civilization from prehistoric times and is the oldest regency among other regencies, which are in Southeast Sulawesi. Muna Regency is one of the areas included in the designation of historical and cultural tourism as a historical and cultural tourism area under regulation Number 2 of 2014-2034 concerning the Muna Regency RTRW. The existence of tourist objects that are quite potential but do not meet the standard criteria so that a container is needed in the form of the availability of facilities and infrastructure equipped with public facilities and other supporting materials can be a tour package and development in various cultural festival activities that will make it a central place for art and cultural festival activities in Muna Regency, especially by using contemporary architectural concepts.